IMPLEMENTASI ANALYTICAL HIERARCHY PROCESS DALAM MENENTUKAN TINGKAT KEPUASAN PELAYANAN E-KTP (STUDI KASUS KANTOR CAMAT PAGAR MERBAU) - Eka Wiyanti; Anita Sindar (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2018)
The implementation of the service of making E-KTP (Electronic Identity Card) in some areas has problems such as data filling, fingerprint recording, retina, photo taking, the reason for blank E-KTP blanks and the bureaucratic structure of E-KTP publishing is often problematic because of the server system . Government agencies in the Pagar Merbau District Head Office do not know specifically the level of community satisfaction in managing the E-KTP. SPK application is used in decision making. The SPK application uses a flexible, interactive, and adaptable CBIS (Computer Based Information System) developed to support solutions to specific, unstructured management problems. The Analytical Hierarchy Process (AHP) method is a method of decision making in solving multicriteria problems. From the AHP calculation, the final result is obtained with the condition that if the value is ≥ 0.4, then the information is Satisfactory Service if 0.4, then the information is Poor Service.